PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN THE PEAK AT SUDIRMAN - Lutfi Aditya; Rivera Pantro Sukma (Human Capital Development, 2015)
Purpose- is to findout the effect of management style and motivation on employee’s performance in the Peak Restaurant Design/methodology/approach- the sample was determined by Slovin formula, primary data were collected by questionaire, and analyzed by multiple regression Findings- The strong coorelation between management style and motivation to boost employee’s performance Research limitations-The limited variables were still dominated by unassigned variables in this research Practical implications-The compensation and motivation are categoried as initial step to boost staff motivation in this company Originality- The excelusivity of this resarch is tending to provide the originality and benefits to the company